2011
DOI: 10.1007/s11033-011-1140-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence in wild population of Labeo rohita (Hamilton, 1822) from nine Indian rivers, analyzed through MtDNA cytochrome b region

Abstract: The present study examined partial cytochrome b gene sequence of mitochondrial DNA for polymorphism and its suitability to determine the genetic differentiation in wild Labeo rohita. The 146 samples of L. rohita were collected from nine distant rivers; Satluj, Brahmaputra, Son, Chambal Mahanadi, Rapti, Chauka, Bhagirathi and Tons were analyzed. Sequencing of 307 bp of Cyto b gene revealed 35 haplotypes with haplotype diversity 0.751 and nucleotide diversity (π) 0.005. The within population variation accounted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Partial mtDNA variation (Luhariya et al, 2012) and allozyme marker analysis (Rana et al, 2004) in rohu from Indo Gangetic region also revealed high level of genetic diversity. However, low level of genetic variation in natural population of L. rohita has been reported in Bangladesh (Alam et al, 2009).…”
Section: Rivermentioning
confidence: 92%
See 1 more Smart Citation
“…Partial mtDNA variation (Luhariya et al, 2012) and allozyme marker analysis (Rana et al, 2004) in rohu from Indo Gangetic region also revealed high level of genetic diversity. However, low level of genetic variation in natural population of L. rohita has been reported in Bangladesh (Alam et al, 2009).…”
Section: Rivermentioning
confidence: 92%
“…Owing to their advantages such as high level of polymorphism, co dominance, even distribution in the genome and easy analysis using PCR, microsatellites are the markers of choice for resolving genetic diversity and phylogenetic relationship in a wide range of taxonomic group (Goldstein and Schlotterer, 1999;Jerry et al, 2006). Use of DNA markers in population genetic studies of rohu is limited to allozyme (Rana et al, 2004) and mtDNA (Luhariya et al, 2012). However, no studies of Indian rohu population have so far been carried out using microsatellite markers.…”
Section: Introductionmentioning
confidence: 99%
“…However, significant genetic differentiation was not detected in Chitala chitala on Ganga river [22]. Similarly, differentiation of haplotypes in L. rohita was significant for genetic structuring of 09 populations of 09 Indian rivers [23]. The success of conservation of an organism and effective management policies depend on the level of genetic divergence within and between species and developing strategies to maintain the natural genetic diversity [24].…”
Section: Resultsmentioning
confidence: 99%
“…A common objective of molecular genetics analysis is to diagnose the differences among presumed stocks in either nuclear allelic types or mtDNA haplotypes (Danzmann and Ihssen, 1995). Use of DNA markers in population genetic studies of rohu is limited to allozyme (Rana et al, 2004) and mtDNA (Luhariya et al, 2012). Nowadays, microsatellites have become the marker of choice for application in fish population genetic studies (Beckmann and Soller, 1990) and can be used to detect genetic introgression in a species.…”
Section: Accordingmentioning
confidence: 99%